2023
DOI: 10.1021/acs.jchemed.2c00614
|View full text |Cite
|
Sign up to set email alerts
|

Atomizados”: An Educational Game for Learning Atomic Structure. A Case Study with Grade-9 Students with Difficulties Learning Chemistry

Abstract: Alternative teaching methodologies are required for grade-9 students diagnosed with difficulties learning chemistry. This study examines the progress made in learning atomic structure by 11 Spanish Students Diagnosed with Learning Difficulties (SDLD, experimental group), including those with poor academic performance, specific learning difficulties in reading, writing, and mathematics, attention deficit hyperactivity disorder, and borderline intellectual disability according to the Spanish curriculum. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Similarly, Badajos et al 12 revealed that the students learning simple monosaccharide classification through games attained significantly higher post-test scores on the assessment tasks because of the positive learning experiences. Finally, Giroń-Gambero and Franco-Mariscal 13 confirmed that games could even enhance the learning of the atomic structure, including constituent particles, ions, and isotopes, among students diagnosed with learning difficulties.…”
Section: ■ Introductionmentioning
confidence: 84%
“…Similarly, Badajos et al 12 revealed that the students learning simple monosaccharide classification through games attained significantly higher post-test scores on the assessment tasks because of the positive learning experiences. Finally, Giroń-Gambero and Franco-Mariscal 13 confirmed that games could even enhance the learning of the atomic structure, including constituent particles, ions, and isotopes, among students diagnosed with learning difficulties.…”
Section: ■ Introductionmentioning
confidence: 84%
“…To address this challenge, game-based learning offers interactive and enjoyable experiences that motivate students to meet specific goals while experimenting and learning. This method also helps students to develop teamwork, communication, collaboration, problem-solving, and planning skills. , We implemented the activity reported by Driscoll and co-workers to explain Li-ion batteries and ion intercalation using stacking block sets (Figure b) . This approach explains essential concepts:…”
Section: Teaching and Learning Methodsmentioning
confidence: 99%
“…The percentages for each score on the Likert scale were calculated for each item (Figure and Tables S1–S4). A further analysis was performed to group the percentages of students who agreed (green) or strongly agreed (blue) with positive attitude items, those who disagreed (orange) or strongly disagreed (red) with negative attitude items, and those who neither agreed nor disagreed (yellow) with moderate attitude items. A detailed analysis of each attitude statement is provided below, along with the positively worded items (Figure ).…”
Section: Evaluation Of the Gamementioning
confidence: 99%